(untitled) (Homoeopathy for All, 2024)
Heat stroke is a potentially fatal medical condition marked by a sudden rise in body temperature, frequently above 104°F (40°C), and malfunctioning of the central nervous system. Rapid cooling and supportive care are the mainstays of conventional treatment, although complementary and alternative therapies like homeopathy are gaining popularity. An extensive analysis of homeopathy’s application in the treatment of heat stroke is given in this article. When treating heat stroke, homeopathy takes a comprehensive approach, taking into account each patient’s unique symptoms and constitutional makeup. The patient’s particular symptoms, such as a high fever, headache, confusion, and dehydration, are taken into consideration while choosing a course of action. Clinical research and case studies indicate that homeopathic remedies can help reduce symptoms, speed up recovery, and avoid problems related to illness when used promptly and effectively.